The Apple (Malus domestica, Rosaceae) - Ali Sarkhosh; Timothy E. Crocker; W. B Sherman; Jeffrey G. Williamson; Juanita Popenoe (EDIS)
Apple growing in Florida was once limited to northern areas where a few local selections of medium to poor quality were grown (Figure 1). These selections fruited well only after the coldest winters. Northern apple cultivars such as ‘Red Delicious’, ‘Golden Delicious’, and ‘McIntosh’ do not produce well in Florida. The main problem is that these selections receive insufficient cold during the winter and, therefore, are slow, weak growing and fruit poorly when grown in Florida. This 4-page fact sheet is a minor revision written by A. Sarkhosh, T. E. Crocker, W. B. Sherman, J. G. Williamson, and J. Popenoe, and published by the Horticultural Sciences Department, May 2019.